2017
DOI: 10.1093/mnras/stx2257
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mass-ratio distribution of spectroscopic binaries – I. A novel algorithm

Abstract: We developed a novel direct algorithm to derive the mass-ratio distribution (MRD) of short-period binaries from an observed sample of single-lined spectroscopic binaries (SB1). The algorithm considers a class of parameterized MRDs and finds the set of parameters that best fits the observed sample. The algorithm consists of four parts. First, we define a new observable, the 'modified mass function', that can be calculated for each binary in the sample. We show that the distribution of the modified mass function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…We reformulate the analysis by defining a unit-less observational parameter 'Astrometric Mass-Ratio Function' (AMRF), A, of a binary, based on primary-mass estimation, in addition to the astrometric parameters. This is similar to the spectroscopic reduced mass function of Shahaf et al (2017). We show how one can use this parameter for studying the mass ratio of a binary, provided the primary is an MS star.…”
Section: Introductionsupporting
confidence: 59%
“…We reformulate the analysis by defining a unit-less observational parameter 'Astrometric Mass-Ratio Function' (AMRF), A, of a binary, based on primary-mass estimation, in addition to the astrometric parameters. This is similar to the spectroscopic reduced mass function of Shahaf et al (2017). We show how one can use this parameter for studying the mass ratio of a binary, provided the primary is an MS star.…”
Section: Introductionsupporting
confidence: 59%
“…Instead, the resulting distribution suggests a linear increase in log q, implying a tendency towards low-q values. Figure 5 compares the modified mass function distribution (Shahaf et al 2017) both with a mass-ratio distribution of a desert-shape and a linear distribution in log q. The figure demonstrates the capacity of the modified mass function to follow the mass-ratio distribution in both cases.…”
Section: The Mass-ratio Distribution Of the K-dwarf Sb1smentioning
confidence: 96%
“…To overcome this problem one needs to apply statistical tools that utilize the assumed spherical symmetry of the binary inclinations (e.g., Boffin et al 1993;Curé et al 2015; Van der Swaelmen et al 2017). One of these tools is the modified mass function of single-lined spectroscopic binaries (SB1s), suggested recently by Shahaf et al (2017). They showed that this parameter, when derived for a sample of SB1s, follows the underlying mass-ratio distribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mass of the primary can be independently estimated, so that the observations determine the minimum value of the mass ratio, qmin, defined as the value of q that corresponds to an edge-on orbit (i = π/2). In contrast, for double-lined spectroscopic binaries, the additional data available allow for an estimate of the inclination angle and hence q itself (see also Shahaf et al 2017 for a detailed discussion of the observational complexities). The observational data from the aforementioned sample are presented in Figure 2, which plots the estimated mass ratios versus the semimajor axes of the systems.…”
Section: Comparison With Observationsmentioning
confidence: 99%